The Influence of Transformational Leadership, Human Relations and Work Ethic on Employee Performance through ASN Job Satisfaction of theMedan Class I Railway Engineering Center - Putra Ramadhan; M. Chaerul Rizky; Sri Rahayu (CV. Doki Course and Training, 2026)
This study aims to analyze the influence of Transformational Leadership, Human Relation, and Work Ethic on Employee Performance through Job Satisfaction in ASN of the Medan Class I Railway Engineering Center. The background of this research is based on the importance of improving the performance of ASN which is influenced by internal organizational factors, such as leadership style, work relationships, quality of work ethic, and employee satisfaction with their work environment. This study uses a quantitative approach with the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The research population was 141 ASN, and a sample of 58 respondents was determined through the Slovin formula. Data was obtained through a questionnaire and analyzed using SmartPLS. The results of the study show that Work Ethic has a positive and significant effect on Job Performance and Satisfaction. Human Relations also has a positive and significant effect on Performance and Job Satisfaction, while Job Satisfaction has been proven to have a positive and significant effect on Employee Performance. On the other hand, Transformational Leadership has a positive but insignificant influence on Performance and Job Satisfaction. Other findings suggest that Job Satisfaction only significantly mediates the relationship between Human Relations and Employee Performance, while the relationship between Work Ethic and Transformational Leadership to Performance is not significantly mediated by Job Satisfaction. Overall, this study emphasizes that improving work relationships and strengthening work ethic are the main factors in improving the performance of ASN of the Medan Class I Railway Engineering Center.